Jaunty Jock, and Other Stories - Munro, Neil, 1864-1930 (Salt Lake City, UT : Project Gutenberg, 2015)
"Jaunty Jock and Other Stories" by Neil Munro is a collection of short stories likely written in the early 20th century. These tales are set primarily in Scotland and explore the lives, humor, and conflicts of its characters, reflecting on societal norms and the relationships between individuals within the community. The lead story, "Jaunty Jock," introduces an intriguing character named Macdonald, who grapples with his own plainness and the expectations of society while navigating the complexities of a social dance. The opening of "Jaunty Jock" immerses the reader in a lively description of a ball in Edinburgh during a rainy November night. The protagonist, Macdonald, struggles with feelings of awkwardness and disdain as he observes the superficiality of his surroundings, including his cousin's flirtations and Lady Charlotte, the organizer of the dance. The narrative transitions from the dance to a fire that erupts in their lodging house, provoking a sense of urgency as Macdonald and his cousin face chaos and danger. This set of events establishes a blend of humor and drama, foreshadowing character development and the interplay of wit and social commentary that is likely to unfold throughout the collection. (This is an automatically generated summary.)
Jaunty Jock -- Young Pennymore -- A return to nature -- The brooch -- The First-foot -- Isle of Illusion -- The Tudor cup -- "Copenhagen": a character -- The silver drum -- The Scottish Pompadour -- The tale of the boon companion.
Release date is 2015-11-12
This ebook was transcribed by Les Bowler
Keywords: Short stories; Scotland -- Social life and customs -- Fiction; Scots -- Foreign countries -- Fiction